Anxiety and Depression Among Adults and Children With Celiac Disease: A Meta‐Analysis of Different Psychiatry Scales - Mostafa Hossam‐Eldin Moawad; Ibrahim Serag; Mahmoud Mohamed Shalaby; Mohamed Smail Aissani; Mohammed Ahmed Sadeq; Nada Ibrahim Hendi; Bashaer Elawfi; Reem Mohamed Farouk Ghorab; Naydeen Mostafa; Nancy Ibrahim; Hasnaa Ali Hassan Abdelrhem; Ahmed Hassan A. Rady; et al. (Psychiatric Research and Clinical Practice)
Background Celiac disease (CD) is an autoimmune disorder in which genetically susceptible individuals cannot digest gluten (wheat) and its homologs such as Scalin (rye) and Hordein (barley). Aim This systematic review and meta‐analysis aimed to investigate the measures of associations between CD and psychiatric disorders, specifically anxiety and depression, and explore the relationship between adherence to a Gluten‐Free Diet (GFD) and the psychiatric aspects of the disease. Methods We searched PubMed, Scopus and Web of Science for articles investigating anxiety and depression in CD patients. The following inclusion criteria were implemented: Primary research articles (either observational or experimental) that include participants with a CD diagnosis ‐confirmed either serologically, with anti‐endomysial antibodies, anti‐tissue transglutaminase antibodies, or with duodenum biopsy, whether on a GFD or not,—who have depression or anxiety symptoms identified through self‐report or clinician‐administered scales. Results CD patients are at a higher odds of developing anxiety, as the odds ratio was (OR: 2.26, 95% CI: [1.10, 4.67]) and depression symptoms (OR: 3.36, 95% CI: [1.36, 8.32]). Results of both State‐Trait Anxiety Inventory Y‐1 and Y‐2 improved after 1 year of GFD with mean difference of 3.48, 95% CI: (0.26, 6.71), and MD: 3.45, 95% CI: (1.39, 5.52), respectively. Conclusion Anxiety and depression are prevalent among adults and children CD patients as they are observed to have high odds of anxiety and depression as expressed by various scales. It is reported that GFD is associated with decreased levels of anxiety and depression, however, further studies are required to confirm these findings and to investigate the main mechanism of psychiatric disorders among CD patients.